2016
DOI: 10.1080/14756366.2016.1238362
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of chiral pyrazolo[4,3-e][1,2,4]triazine sulfonamides with tyrosinase and urease inhibitory activity

Abstract: A new series of sulfonamide derivatives of pyrazolo[4,3-e][1,2,4]triazine with chiral amino group has been synthesized and characterized. The compounds were tested for their tyrosinase and urease inhibitory activity. Evaluation of prepared derivatives demonstrated that compounds (8b) and (8j) are most potent mushroom tyrosinase inhibitors whereas all of the obtained compounds showed higher urease inhibitory activity than the standard thiourea. The compounds (8a), (8f) and (8i) exhibited excellent enzyme inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Noreen et al recently reported thiophene-tagged sulfonamides as µg/mL concentration urease inhibitors. Mojzych et al published pyrazoletriazine- based sulfonamides as dual potent inhibitors of urease and tyrosinase and their synthesized derivatives showed better potential than standard thiourea, with IC 50 values in the micromolar range [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noreen et al recently reported thiophene-tagged sulfonamides as µg/mL concentration urease inhibitors. Mojzych et al published pyrazoletriazine- based sulfonamides as dual potent inhibitors of urease and tyrosinase and their synthesized derivatives showed better potential than standard thiourea, with IC 50 values in the micromolar range [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the sulfonamide bearing derivatives had tyrosine kinase and carbonic anhydrase inhibitory actions. The activity of both compounds 5a and 5b against tyrosinase was with IC 50 30.76 and 27.90 μM (Mojzych et al, ).…”
Section: Synthesis and Anticancer Activity Of Nostocine Derivativesmentioning
confidence: 99%
“…A series of pyrazolotriazine containing sulfonamide functionality with the presence of amino chiral center in the structure (4 , 6) exhibited an inhibitory action on tyrosine kinase, which is associated with cancer producing enzymes. Among all synthesized compound, 4‐ethoxy substiuted N ‐propanyl benzene sulfonamide at C‐5 position of pyrazolotriazine moiety (5) had a greater tyrosine inhibitory action, but it had a weak urease inhibitory action (Mojzych et al, ).…”
Section: Sar Of Nostocine Derivatives With Anticancer Activitymentioning
confidence: 99%
“…Due to the critical role of tyrosinase in the melanogenesis process, it becomes an attractive target for medicinal chemists to develop inhibitors applied in cosmetics and pharmacological therapy ( Larik et al, 2017 ). Recently, different research groups have engaged in the discovery of tyrosinase inhibitors, and several new types of molecules were disclosed ( Ashraf et al, 2015 ; Choi et al, 2014 ; Haudecoeur et al, 2017 ; Mojzych et al, 2017 ; Park et al, 2013 ; Ruzza et al, 2016 ; Tan et al, 2016 ; Wang et al, 2016 ; Wu et al, 2017 ; You et al, 2015 ). These findings provide opportunity for the subsequent medicinal optimization.…”
Section: Introductionmentioning
confidence: 99%